2019
DOI: 10.1186/s13039-019-0433-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of copy number variations induced by ultrashort electron beam radiation in human leukocytes in vitro

Abstract: Background Environmental risk factors have been shown to alter DNA copy number variations (CNVs). Recently, CNVs have been described to arise after low-dose ionizing radiation in vitro and in vivo. Development of cost- and size-effective laser-driven electron accelerators (LDEAs), capable to deliver high energy beams in pico- or femtosecond durations requires examination of their biological effects. Here we studied in vitro impact of LDEAs radiation on known CNV hotspots in human peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The authors claim that gains and losses of cancer-related candidate genes and miRNAs observed in studied cohort have the potential to allow identification of radiation-associated breast cancer at the individual level [37]. Interestingly, gains in chromosomal region 7q11.22 were also observed in our study of radiation-induced CNVs in human leukocytes in vitro [25] indicating feasibility of CNVs in this locus for detection of radiation exposure in human cells.…”
Section: Radiation-induced Cnvs In Vivomentioning
confidence: 54%
See 1 more Smart Citation
“…The authors claim that gains and losses of cancer-related candidate genes and miRNAs observed in studied cohort have the potential to allow identification of radiation-associated breast cancer at the individual level [37]. Interestingly, gains in chromosomal region 7q11.22 were also observed in our study of radiation-induced CNVs in human leukocytes in vitro [25] indicating feasibility of CNVs in this locus for detection of radiation exposure in human cells.…”
Section: Radiation-induced Cnvs In Vivomentioning
confidence: 54%
“…We studied CNVs in chromosomal regions 1p31.1, 7q11.22, 9q21.3, 10q21.1 and 16q23.1 in cultured normal human blood leukocytes irradiated with laser-driven electron bunches using parental origin determination FISH (POD-FISH) [25]. Irradiation of cells significantly increased levels of duplication in all analyzed chromosomal regions earlier reported to be sensitive to ionizing radiation.…”
Section: Radiation-induced Cnvs In Vitromentioning
confidence: 99%
“…The investigations on the biological effect/effectiveness of conventional, not laserdriven, accelerators have been conducted for several decades [12][13][14][15][16][17][18]. However, since ultrashort pulsed laser-driven electron accelerators are relatively new, data about their radiobiological effect is very limited in the literature, and the existing studies are mostly related to in vitro studies [19][20][21][22][23][24]. Thus, laser-driven UPEB irradiation has been shown to induce molecular-cytogenetically visible copy number variations (CNVs) [19], increase micronucleus frequency, and shorten telomere length in healthy human peripheral blood lymphocytes [18,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, since ultrashort pulsed laser-driven electron accelerators are relatively new, data about their radiobiological effect is very limited in the literature, and the existing studies are mostly related to in vitro studies [19][20][21][22][23][24]. Thus, laser-driven UPEB irradiation has been shown to induce molecular-cytogenetically visible copy number variations (CNVs) [19], increase micronucleus frequency, and shorten telomere length in healthy human peripheral blood lymphocytes [18,25]. In the human ovarian cancer cell line OVCAR-3, it was shown to reduce the cell survival [25].…”
Section: Introductionmentioning
confidence: 99%
“…Metaphase chromosomes were prepared as previously described [ 38 ]. Forty-eight hours after culture initiation, DOX was added at concentrations of 0.025, 0.035 and 0.05 µg/mL and incubated for 24 h. Colcemid (0.1 μg/mL final concentration; Merck, Germany) was added to the culture 1.5 h before harvesting and incubated at 37 °C to achieve metaphase block.…”
Section: Methodsmentioning
confidence: 99%